Analisis Flypaper Effect pada Pengaruh Pendapatan Asli Daerah (PAD), Dana Alokasi Umum (DAU), Dana Alokasi Khusus (DAK), dan Sisa Lebih Pembiayaan Anggaran (SiLPA) terhadap Belanja Daerah: Studi Empiris pada Pemerintah Kabupaten/Kota se Provinsi Sumatera - Rahmat Nur Rafi; Fefri Indra Arza (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to examine the effect of PAD, DAU, DAK and SILPA on Regional Expenditures, besides that it also examines whether the FLYPAPER EFFECT phenomenon occurs in local governments in West Sumatra. The population in this study is the Indonesian Provincial Government in 2016-2020. The analytical method used is multiple linear regression analysis. The results of this study indicate that PAD, DAU, DAK, and SILPA have a significant effect on Regional Expenditures and also the occurrence of the FLYPAPER EFFECT phenomenon in local government in West Sumatra.